Pelatihan Mengoperasikan Kit Pembelajaran bagi Guru SD di Kota Palangka Raya - Rita Rahmaniati; Bulkani Bulkani; Fazakkir Noor (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
The aim of this dedication is to improve the teachers’ professionalism in using elementary learning media/KIT in the city of Palangkaraya. The method of this activity used in the form of training/workshop and the training results are presented by each teacher group, through stages 1) lecture 2) simulation 3) exploration 4) mentoring and 5) evaluation. The target audience or training participants were the classroom teachers and subject teachers at Muhammadiyah Elementary School in Palangkaraya city, as many as 19 people and also involves some of the university students who have been trained using elementary learning KIT correctly. The result of this dedication activity showed that: the ability of teachers in Elementary School of Muhammadiyah Pahandut Palangkaraya is 90% teachers has been skilled to both operate learning KIT and 10% teachers in enough category and still need more guidance in operating KIT Learning.